(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
Median rhomboid glossitis manifests as a well-delineated erythematous area located along the midline posterior dorsal tongue. Its rhomboid shape usually "points" in an antero-posterior direction. Median rhomboid glossitis may have a "kissing lesion," or area of roughness, most commonly in the area of the hard and soft palate. Here is a case report of 24 year old male patient having median rhomboid glossitis with kissing lesions over the hard palate. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20273 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 94-97